Farmers’ Perception on the Welfare of Broiler Chickens in Smallholder Production Systems in Kiambu County, Kenya - Achikule A. Yensuk; Joyce G. Maina; Paul N. Mbugua (Advances in Agriculture)
In Kenya, commercial broiler production is growing rapidly due to increasing demand for poultry meat resulting in higher incomes for farmers. Due to this increase in demand, broiler chicken production is increasingly becoming intensive where chickens are overstocked in deep litter systems subjecting the birds to suffering perpetuated through burns on their shanks and breasts with constant footpad lesions, thus compromising their welfare. This study was conducted to determine the farmers’ attitudes towards the welfare of broiler chickens in smallholder production systems in Kiambu County, Kenya. A total of 120 farmers were randomly chosen for the study consisting of 42 and 78 respondents from Kikuyu and Kabete subcounties, respectively. A semistructured questionnaire was used to interview the farmers on their knowledge, attitudes, and practices in regard to broiler welfare. The results of this study indicated that most farmers (74%) in Kikuyu and Kabete subcounties had knowledge about broiler welfare. Media, hatcheries, agrovet centres, and extension agents were the main sources of information on broiler welfare to farmers at 61%, 40%, 38.8%, and 31.5% respectively. Farmers perceived that good feeding (88%), good health (83%), suitable housing (82%), and appropriate behaviour (48%) were very important indicators of broiler chicken welfare. Gumboro (infectious bursal disease) and new castle disease (NCD) were prevented through vaccination by most farmers (91%), while coccidiosis was controlled through cleaning and disinfection of broiler sheds and equipment as well as treatment of sick birds with coccidiostat. In conclusion, farmers’ perception on broiler welfare has a bearing on the performance of broiler chickens.